Lactoferrin-based food supplements trigger toxin production of enteropathogenic Bacillus cereus - Jugert, Clara-Sophie; Didier, Andrea; Jessberger, Nadja (Frontiers in Microbiology, 2023)
Lactoferrin is an iron-binding glycoprotein exhibiting antibacterial, antiviral, antifungal, antiparasitic, antiinflammatory, antianaemic and anticarcinogenic properties. While its inhibitory effects against bacterial pathogens are well investigated, little is known about its influence on the production and/or mode of action of bacterial toxins. Thus, the present study aimed to determine the impact of food supplements based on bovine lactoferrin on Bacillus cereus enterotoxin production. First, strain-specific growth inhibition of three representative isolates was observed in minimal medium with 1 or 10 mg/mL of a lactoferrin-based food supplement, designated as product no. 1. Growth inhibition did not result from iron deficiency. In contrast to that, all three strains showed increased amounts of enterotoxin component NheB in the supernatant, which corresponded with cytotoxicity. Moreover, lactoferrin product no. 1 enhanced NheB production of further 20 out of 28 B. cereus and Bacillus thuringiensis strains. These findings again suggested a strain-specific response toward lactoferrin. Product-specific differences also became apparent comparing the influence of further six products on highly responsive strain INRA C3. Highest toxin titres were detected after exposure to products no. 7, 1 and 2, containing no ingredients except pure bovine lactoferrin. INRA C3 was also used to determine the transcriptional response toward lactoferrin exposure via RNA sequencing. As control, iron-free medium was also included, which resulted in down-regulation of eight genes, mainly involved in amino acid metabolism, and in up-regulation of 52 genes, mainly involved in iron transport, uptake and utilization. In contrast to that, 153 genes were down-regulated in the presence of lactoferrin, including genes involved in flagellar assembly, motility, chemotaxis and sporulation as well as genes encoding regulatory proteins, transporters, heat and cold shock proteins and virulence factors. Furthermore, 125 genes were up-regulated in the presence of lactoferrin, comprising genes involved in sporulation and germination, nutrient uptake, iron transport and utilization, and resistance. In summary, lactoferrin exposure of B. cereus strain-specifically triggers an extensive transcriptional response that considerably exceeds the response toward iron deficiency and, despite down-regulation of various genes belonging to the PlcR-regulon, ultimately leads to an increased level of secreted enterotoxin by a mechanism, which has yet to be elucidated.